Design Study on Customised Piezoelectric Elements for Energy Harvesting in Total Hip Replacements - Hans-E. Lange; Rainer Bader; Daniel Kluess (Energies, 2021)
Energy harvesting is a promising approach to power novel instrumented implants that have passive sensory functions or actuators for therapeutic measures. We recently proposed a new piezoelectric concept for energy harvesting in total hip replacements. The mechanical implant safety and the feasibility of power generation were numerically demonstrated. However, the power output for the chosen piezoelectric element was low. Therefore, we investigated in the present study different geometry variants for an increased power output for in vivo applications. Using the same finite element model, we focused on new, customised piezoelectric element geometries to optimally exploit the available space for integration of the energy harvesting system, while maintaining the mechanical safety of the implant. The result of our iterative design study was an increased power output from 29.8 to 729.9 µW. This amount is sufficient for low-power electronics.